A ferrocenyl pyridine-based Ru(ii) arene complex capable of generating ·OH and 1O2 along with photoinduced ligand dissociation. Issue 51 (10th May 2016) - Wang, Tianji; Zhou, Qianxiong; Zhang, Yangyang; Zheng, Yue; Wang, Weibo; Hou, Yuanjun; Jiang, Guoyu; Cheng, Xuexin; Wang, Xuesong
Abstract : A ferrocene modified Ru(ii ) arene complex was developed to present dual activity of photoactivated chemotherapy (PACT) and photodynamic therapy (PDT). Abstract : Photoactivated chemotherapy (PACT) and photodynamic therapy (PDT) are two types of cancer treatment modalities that rely on photoinduced ligand dissociation and photosensitized or photocatalyzed reactive oxygen species (ROS) generation to realize anticancer activities with high selectivity, respectively. In this study, a novel Ru complex, [( p -cym)Ru(bpy)(py-Fc )] 2+ (1 ), where p -cym = para -cymene, bpy = 2, 2′-bipyridine, andpy-Fc = 4-pyridyl ferrocene, was demonstrated to show dual activity from PACT and PDT.1 has a long-wavelength absorption band extending to 600 nm and can generate both hydroxyl radicals (·OH) and singlet oxygen ( 1 O2 ) along with photoinduced monodentate ligand dissociation. As a result, 1 displays DNA photocleavage activity as well as phototoxicity against human ovarian adenocarcinoma cells SKOV3 and human lung adenocarcinoma cells A549. The underlying mechanisms were discussed by comparing the photophysical, photochemical, and photobiological properties of1 with that of [( p -cym)Ru(bpy)(py)] 2+ (2, py = pyridine) and freepy-Fc, providing guidelines for developing new photoactivated metallodrugs with multiple functions.